2012
DOI: 10.1128/mcb.06111-11
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids Regulate the Yeast High-Osmolarity Glycerol Response Pathway

Abstract: bThe yeast high-osmolarity glycerol response (HOG) mitogen-activated protein (MAP) kinase pathway is activated in response to hyperosmotic stress via two independent osmosensing branches, the Sln1 branch and the Sho1 branch. While the mechanism by which the osmosensing machinery activates the downstream MAP kinase cascade has been well studied, the mechanism by which the machinery senses and responds to hyperosmotic stress remains to be clarified. Here we report that inhibition of the de novo sphingolipid synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 41 publications
7
61
0
1
Order By: Relevance
“…erg5D mutant has an osmotolerance equivalent to the WT (at 1.4 M NaCl), which is higher relative to erg2D, erg3D, erg4D or erg6D mutants. This should be seen in the light of earlier observations (Tanigawa et al, 2012) that erg2D, erg3D and erg6D mutant exhibit elevated Hog1p phosphorylation due to perturbation of the plasma membrane. However, the hyperosmotic sensitivity of these mutants observed by Kodedov a & Sychrov a, (2015) points to the essential contribution of plasma membrane functions for successful adaptation via HOG signalling.…”
Section: Genetic Regulation Versus Metabolic Adaptationsupporting
confidence: 62%
“…erg5D mutant has an osmotolerance equivalent to the WT (at 1.4 M NaCl), which is higher relative to erg2D, erg3D, erg4D or erg6D mutants. This should be seen in the light of earlier observations (Tanigawa et al, 2012) that erg2D, erg3D and erg6D mutant exhibit elevated Hog1p phosphorylation due to perturbation of the plasma membrane. However, the hyperosmotic sensitivity of these mutants observed by Kodedov a & Sychrov a, (2015) points to the essential contribution of plasma membrane functions for successful adaptation via HOG signalling.…”
Section: Genetic Regulation Versus Metabolic Adaptationsupporting
confidence: 62%
“…Earlier, Reiser et al (2003) observed that the uniform distribution on the cell membrane of Sln1 changed upon osmotic shock, forming clusters. This observation can now be explained by the experiments performed by Tanigawa et al (2012), which indicated that osmotic stress causes a partial dissociation of Sln1 from rafts. Sho1 distribution, on the other hand, was observed to remain unchanged upon osmotic shock (Reiser et al 2003); however, osmotic stress promoted the association of Sho1 to rafts (Tanigawa et al 2012), which was suggested to have an important regulatory role.…”
Section: Yeast and Fungimentioning
confidence: 82%
“…This observation can now be explained by the experiments performed by Tanigawa et al (2012), which indicated that osmotic stress causes a partial dissociation of Sln1 from rafts. Sho1 distribution, on the other hand, was observed to remain unchanged upon osmotic shock (Reiser et al 2003); however, osmotic stress promoted the association of Sho1 to rafts (Tanigawa et al 2012), which was suggested to have an important regulatory role. Further studies would undoubtedly advance our understanding of the proposed osmosensing mechanisms.…”
Section: Yeast and Fungimentioning
confidence: 82%
See 1 more Smart Citation
“…When we performed our simulations, we assumed a linear input that turgor pressure has on the phosphorylation of Sln1, namely the linear decrease in k 1 : Although there is still ongoing research on the topic (Tanigawa et al 2012), the mechanism itself has not been characterized comprehensively. Neither has the stochastic influence of the whole ensemble of Sln1 sensing the external signal been studied.…”
Section: Choosing the Inputmentioning
confidence: 99%